Environmental Parameters in Sediment of Razor Clam Producing Area in Buntal - Lim, Bih Loong (Universiti Malaysia Sarawak (UNIMAS), 2007)
The main objective of this study is to determine the values of environmental parameters in sediment of razor clam producing area in Buntal coastline, Sarawak. Data for parameters of interstitial water quality, total organic matter, and particles size were obtained; conductivity (20.42 to 47.30 µS/cm), dissolved oxygen (5.74 to 6.78 mg/1), percentage of natrium chloride composition (40.70 to 80.73%), pH (7.25 to 7.70), salinity (20 to 30 PSU), temperature (29.57 to 31.50 °C), total dissolved solid (10.02 to 25.23 mg/1), ammonia-nitrogen (1.12 to 4.00 mg/1), nitrate (0.01 to 0.23 mg/1), nitrite (0.0017 to 0.0090 mg/1), orthophosphate (0.01 to 0.04 mg/1), silicate (2.26 to 3.13 mg/1), COD (125.00 to 142.33 mg/1), total organic matter (0.0081 g to 0.0484 g), percentage of sand fraction (84.49 to 91.09 %), percentage of clay fraction (3.20 to 7.15 %), and percentage of silt fraction (2.30 to 4.33 %). Two-Way ANOVA statistical analysis showed there were no significant differences between the two different months for orthophosphate, silicate, percentage of clay fraction, and percentage of silt fraction. The results of this study show that the environmental condition of Buntal coastline is suitable as a habitat for razor clam.